Synthesis and Characterization of Mixed Iron-Manganese Oxide Nanoparticles and Their Application for Efficient Nickel Ion Removal from Aqueous Samples. (19th July 2017) - Buccolieri, Alessandro; Serra, Antonio; Maruccio, Giuseppe; Monteduro, Anna Grazia; Padmanabhan, Sanosh Kunjalukkal; Licciulli, Antonio; Bonfrate, Valentina; Salvatore, Luca; Manno, Daniela; Calcagnile, Lucio; Giancane, Gabriele
Abstract : Mixed iron-manganese oxide nanoparticles, synthesized by a simple procedure, were used to remove nickel ion from aqueous solutions. Nanostructures, prepared by using different weight percents of manganese, were characterized by transmission electron microscopy, selected area diffraction, X-ray diffraction, Raman spectroscopy, and vibrating sample magnetometry. Adsorption/desorption isotherm curves demonstrated that manganese inclusions enhance the specific surface area three times and the pores volume ten times. This feature was crucial to decontaminate both aqueous samples and food extracts from nickel ion. Efficient removal of Ni 2+ was highlighted by the well-known dimethylglyoxime test and by ICP-MS analysis and the possibility of regenerating the nanostructure was obtained by a washing treatment in disodium ethylenediaminetetraacetate solution.